Clow-code platforms: democratizing development or creating a delayed danger - Chaimae Michich; Kadatska, O. (ХНУРЕ, 2025)
Low-code platforms have revolutionized software development by enabling non-technical users to build applications. However, their ease of use often bypasses traditional security safeguards, creating systemic vulnerabilities. This article analyzes security risks in low-code ecosystems, including shadow IT, insecure integrations, and compliance gaps. Using real-world case studies, we propose mitigation strategies such as centralized governance and DevSecOps integration to balance agility with security.
Keywords: Clow-code platform; creating a delayed danger